The archaeology of death : proceedings of the Seventh Conference of Italian Archaeology held at the National University of Ireland, Galway, April 16-18, 2016 - Herring, Edward; O'Donoghue, Eoin (Papers in Italian archaeology, 2018)
This volume collects more than 60 papers by contributors from the British Isles, Italy and other parts of continental Europe, and North and South America, focusing on recent developments in Italian archaeology from the Neolithic to the modern period.